If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(x + y) = 4y + y (x * 4 + y * 4) = 4y + y (4x + 4y) = 4y + y Combine like terms: 4y + y = 5y 4x + 4y = 5y Solving 4x + 4y = 5y Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4y' to each side of the equation. 4x + 4y + -4y = 5y + -4y Combine like terms: 4y + -4y = 0 4x + 0 = 5y + -4y 4x = 5y + -4y Combine like terms: 5y + -4y = 1y 4x = 1y Divide each side by '4'. x = 0.25y Simplifying x = 0.25y
| 4x-3y-6z=6 | | -16y=6 | | 40/5=-4x | | 130+20+x=180 | | -35/7=27x | | H=bf | | -35/7=4(6x) | | 8(-2x)-4x=-40 | | 69+2x=769 | | 8x+2(3x)=56 | | -3=6(-4x) | | 4(4x)=48 | | 5/3y=35 | | x+3x=380 | | x+14x=80 | | x+2x=330 | | -5=x/8 | | 7x-7-6x+1=-2+6 | | 2b-11=10-c | | 13-17=8y+6-7y | | 13x-5-12x-5=-11 | | -2+16=a+6-5 | | 7x-2(-10)=4 | | 1-9=x-2+16 | | 1=3+d | | -x/2-2/2 | | v+4=-2(x-1) | | x^2-2xy+y^2-m^2-2mn-n^2= | | -36s^3t-26st/-2tst=0 | | -36s^3t-26st/-2tst | | 4050=27000*.05*t | | -1=m/32 |